Cross-nat - Kyle John Wilby; Kerry Wilbur (Elsevier, 2017)
Background: Access to narcotics has been described as suboptimal in the Middle East. The objectives of this study were to characterize estimated narcotic use in twelve Arabic-speaking nations and compare across world regions. Methods: This was a population-based cross-sectional analysis of estimated average consumption of narcotic drugs in defined daily doses per million inhabitants, as provided by the International Narcotics Control Board Technical Reports (2008-2012). Five years of data (2008-2012) were extracted from reports for 12 Arabic-speaking countries: Lebanon, Jordan, Syria, Qatar, United Arab Emirates, Saudi Arabia, Oman, Bahrain, Kuwait, Iraq, Egypt, and Yemen. Data were also obtained for world regions. Results: In 2012, Bahrain and Kuwait had the highest estimates (364 and 352 defined daily doses per million inhabitants per day, respectively), while Yemen and Iraq had the lowest (9 and 6 defined daily doses per million inhabitants per day, respectively). North America, Oceania, and Europe had the highest rates (32,264, 9978, and 7937 defined daily doses per million inhabitants per day, respectively), while Arabic-Countries were only ahead of Africa and Central America (128, 91, 87 defined daily doses per million inhabitants per day, respectively). Conclusions: Great variability was observed in estimates between 12 Arabic countries and even larger disparity when Arabic-Countries were benchmarked against world regions, suggesting a need for future studies to determine reasons for these discrepancies.